Construction of Multidimensional Stochastic Transformation Blocks - Chugunkov, Ilya V.; Kliuchnikova, Bogdana V.; Yadykin, Igor M.; Gulyaev, Vadim A.; Chugunkov, Vladimir I. (2019 International Conference "Quality Management, Transport and Information Security, Information Technologies" (IT&QM&IS), 2019)
The article is devoted to the improvement of stochastic transformation blocks (R-blocks). The principles of R- blocks construction are considered. We review the examples of R- blocks using in the cryptographic algorithms. The structure of two-dimensional stochastic transformation block is proposed, as well as the method for construction of multidimensional R- blocks. The using of improved R-blocks for construction of multidimensional algorithms is proposed. The results of evaluation of statistical properties of the multidimensional stochastic transformation blocks are given.